Historia de la Provincia de la Compañía de Jesus de Nueva España - Alegre, Francisco Javier (Bibliotheca Instituti Historici S.I, 1956)
1. Libros 1-3 (Anos 1566-1596)- 2. Libros 4-6 (Anos 1597-1639)- 3. Librois 7-8 (Años 1640-1675)- 4. Libros 9-10 (Años 1676-1766)